2015
DOI: 10.3389/fmicb.2015.01391
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Appearance of Oral Candida Infection and Therapeutic Strategies

Abstract: Candida species present both as commensals and opportunistic pathogens of the oral cavity. For decades, it has enthralled the clinicians to investigate its pathogenicity and to improvise newer therapeutic regimens based on the updated molecular research. Candida is readily isolated from the oral cavity, but simple carriage does not predictably result in development of an infection. Whether it remains as a commensal, or transmutes into a pathogen, is usually determined by pre-existing or associated variations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
242
0
61

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(307 citation statements)
references
References 66 publications
4
242
0
61
Order By: Relevance
“…In our study, thirty-eight patients reported sleeping with the dentures, among a total of forty. This habit is harmful because the contact of the contaminated surface of the denture with the palatal mucosa is continuous, favoring the reduction of salivary flow and the development of denture stomatitis [2, 8, 3638]. Studies show that only the drug treatment of the patient is not effective, and disinfection of the denture surface is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, thirty-eight patients reported sleeping with the dentures, among a total of forty. This habit is harmful because the contact of the contaminated surface of the denture with the palatal mucosa is continuous, favoring the reduction of salivary flow and the development of denture stomatitis [2, 8, 3638]. Studies show that only the drug treatment of the patient is not effective, and disinfection of the denture surface is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…It is only painful form of candidiasis. (1,11) Lesions on dorsum of tongue result in loss of papilla. Differential diagnosis includes denture stomatitis, erythema migrans, erythroplakia and anemia.…”
Section: Classificationmentioning
confidence: 99%
“…It can also occur in association with iron and folate deficiencies and with defective cell mediated immunity. (1) Other forms of candidiasis Denture stomatitis: It is chronic inflammation of mucosa mainly restricted to denture area, so also known as chronic atrophic candidiasis. It is seen in 50-65% of patients wearing dentures.…”
Section: Classificationmentioning
confidence: 99%
See 2 more Smart Citations